The current treatment strategies for autoimmune diseases, including immunosuppressive drugs, biologics and emerging immunotherapies like CAR-T cell therapy - Bandyopadhyay, Syamasis (International Journal of Research in Medical Sciences, 2024)
This review explores the evolving strategies in autoimmune disease (AID) management, focusing on the limitations of traditional therapies and the potential of emerging treatments. Traditional treatments, including corticosteroids, NSAIDs and DMARDs, are effective but often fail to restore immune tolerance and come with significant side effects. Emerging therapies, such as Janus kinase (JAK) inhibitors and sphingosine-1-phosphate (S1P) receptor modulators, offer targeted approaches by disrupting specific inflammatory pathways. Chimeric Antigen Receptor–T Cell (CAR-T) therapy, originally developed for cancer, is being investigated for AIDs, showing promise in targeting and eliminating autoreactive immune cells. Despite their benefits, these advanced therapies face challenges such as high costs and complex administration. This explored the role of biosimilars, like Exemptia, a biosimilar of Adalimumab, in addressing these challenges. By providing a cost-effective alternative without compromising efficacy or safety, biosimilars expand access to effective biologic therapies for AID management.